MODEL STRUKTURAL HUBUNGAN BUDAYA ORGANISASI, KOMPETENSI PENGGUNA, PENGENDALIAN INTERNAL DAN KUALITAS INFORMASI AKUNTANSI PEMERINTAH DAERAH - Rima Rachmawati (MIX: JURNAL ILMIAH MANAJEMEN, 2018)
Abstract. This study aims to prove the influence of organizational culture, usercompetence and internal control to the quality of Regional Financial ManagementInformation Sistem (abbreviation=SIPKD), and to also prove the quality of SIPKDrelationship to the quality of accounting information. Survey in Garut local governmentas many as 75 of SIPKD users. Data analysis using Structural Equation Modeling(SEM) with Partial Least Square approach (PLS). The SEM PLS consists of twoevaluation; inner model and structural model. The result of the research indicate thatthere is an effect of internal control on the creation of quality SIPKD, and qualitySIPKD can influence the creation of quality accounting information. While theorganization culture and user competence is not proven to influence the creation ofquality SIPKD. Research implications can solve the problem of accounting informationsistems, especially in the local government of Garut.